The book of road-tested activities - Biech, Elaine (San Francisco, CA : Pfeiffer, 2011)
'Training legend Elaine Biech oversees this edited collection of classic activities and games created by stalwarts of the learning community and used successfully for years by professional, front-line trainers. Spanning all types of activities--icebreakers, role-playing, simulations, and energizers--the book covers classic games and activities with new hooks and variations to encourage audience engagement and participation'--
Keywords: Management games; Business communication; Teams in the workplace; Leadership